Cancellous Tibial Bone Graft for Malunion after Mandibular Reconstruction in Head and Neck Cancer. (2nd December 2020) - Hamill, Chelsea S.; Maatouk, Christopher M.; Clancy, Kate; Zender, Chad A.; Rezaee, Rod P.
Abstract : Objectives/ Hypothesis: While nonunion after mandibular reconstruction for head and neck surgery is rare, literature exploring management is scarce. Our primary objective was to determine success rates of tibial bone graft (TBG) in achieving mandibular union. Secondary objectives include determining factors that contribute to failure of TBG. Study Design: Retrospective Chart Review. Methods: Retrospective chart review between January 1, 2008 and December 31, 2018. Patients who underwent a mandibulotomy or mandibulectomy with osteocutaneous free flap reconstruction were identified. Patients who were pursuing dental rehabilitation, subsequently diagnosed with mandibular nonunion and received a cancellous TBG were assessed. Results: The 15 patients meeting inclusion criteria were mostly male (67%), white (87%), and nonsmokers (67%) with a median age of 64 (IQR = 60–73). Successful union occurred in 13 of 18 (72%) TBGs and the majority (63%) had a partial union documented at the time of surgery. Five patients (83%) who initially had a mandibulotomy achieved union compared to 78% of those with osteocutaneous reconstruction ( P = 1.0). Postoperative radiation did not affect rates of union: 80% for both ( P = 1.0). Patients with osteoradionecrosis (ORN) achieved union in 67% of cases compared to 75% of cases who did not have ORN ( P = .86). There were similar rates of union for those who required perioperative antibiotics for infection and those without infection (67% vs. 75%, P = .86). Dental rehabilitation was achieved in 55% of patients, most commonly dentures. Conclusions: This study shows that TBG can be used to achieve union for patients with malunion after head and neck cancer reconstruction. We show its successful use within the reconstructive algorithm for patients regardless of postoperative radiation for very small defects. Level of Evidence: 3 Laryngoscope, 131:1291–1296, 2021